CONCEPTUAL FOUNDATIONS OF THE DEVELOPMENT OF THE FINANCIAL MARKET OF UZBEKISTAN - KADIROVA, KHADICHA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The study of the modern development of the financial market of Uzbekistan, the study of its conceptual foundations. Identification of modern problems of its development. Development of the concept of further development of the regional financial market.